[PP.20.12] SYSTOLIC AND DIASTOLIC DYSFUNCTION AMONG TREATED HYPERTENSIVE PATIENTS: ASSOCIATIONS WITH RESPECT TO HYPERTENSION CONTROL AND TREATMENT RESISTANCE. (September 2016) - Kasiakogias, A.; Tsioufis, C.; Konstantinidis, D.; Georgiopoulos, G.; Andrikou, E.; Vlachos, G.; Kintis, K.; Bazoukis, G.; Kyriazopoulos, K.; Frantzeskakis, A.; Milkas, A.; Thomopoulos, K.; et al.
Abstract : Objective: Uncontrolled as well as apparent resistant hypertension (aRHT) are clinical conditions that deserve a thorough evaluation of heart function to assess the relevant risk profile. We investigated echocardiographic characteristics of patients without symptoms of heart failure with respect to their blood pressure (BP) control status. Design and method: We studied 1094 asymptomatic, treated hypertensives (mean age 58 ± 11 years, 48% males) without a history of cardiovascular disease. Clinical data were collected and patients underwent routine blood testing and additional workup for exclusion of secondary causes of RHT. Uncontrolled HT was defined as office BP > or = 140 and/or 90 mmHg and aRHT as uncontrolled HT under at least 3 drugs including a diuretic. A 2D and Doppler echocardiographic study was performed in all patients and left ventricular mass was calculated and indexed for body surface area (LVMI). Tissue Doppler imaging was performed for calculation of myocardial velocities. Patients were divided into 3 groups depending on BP control and presence of aRHT; 243 (22%) patients with controlled HT, 557 (51%) patients with uncontrolled HT and 294 (27%) patients with RHT. Results: Mean BP was 124 ± 9 mmHg in the controlled HT group while patients with uncontrolled and aRHT had similar BP values (149 ± 13 vs 153 ± 19 mmHg, p = NS). There was no significant difference in the ejection fraction among groups. LVMI was higher in patients with aRHT compared to those with uncontrolled and controlled HT (94 ± 22 vs 87 ± 20 and 85 ± 20 g/m 2, p < 0.001 for all). Concentric hypertrophy/remodelling was more often in patients with aRHT compared to the other groups (25% compared to 12% and 8%, p < 0.001). Patients with aRHT compared to patients with uncontrolled HT had lower values of E/A (0.93 ± 0.24 vs 0.98 ± 0.26 m/sec, p = 0.025), lower values of E' (7.2 ± 2.4 vs 7.8 ± 2.4, p = 0.05) and higher values of E/E' (11.6 ± 4.2 vs 10.3 ± 3.3 cm/sec, p < 0.01). A value of E/E' above 13 was more prevalent in patients with aRHT (26%) compared to those with uncontrolled (21%) and controlled HT (20%). Conclusions: Among asymptomatic treated hypertensives, patients with aRHT exhibit measures of a worse diastolic function compared to patients with uncontrolled hypertension despite similar values of BP.